Combined Isometric Handgrip Exercise and Slow Deep Breathing for Blood Pressure Reduction: A Family Nursing Case Study - Afif Azhar Abulkhair Jayadie; Hiryadi; Sri Sundari (Fakultas Kedokteran, Universitas Papua, 2026)
Hypertension requires continuous management, and family involvement may support self-care and sustained blood pressure control at home. This study aimed to describe the application of combined isometric handgrip exercise and slow deep breathing for blood pressure reduction within the context of family nursing care in a patient with hypertension. This single-case study involved a 59-year-old woman with a five-year history of hypertension. The combined intervention was implemented for 15–20 minutes daily over five consecutive days, with blood pressure measured before and after each session. The patient's blood pressure changed from 193/108 mmHg before the intervention on the first day to 164/92 mmHg after the intervention on the fifth day. The patient also reported reduced shortness of breath and tingling in the right leg, improved sleep quality, and an increased ability to perform the exercise independently. Family members participated by accompanying and encouraging the patient and supporting dietary changes. Combined isometric handgrip exercise and slow deep breathing may be considered an adjunctive non-pharmacological approach within family nursing care for patients with hypertension.